Gastric squamous-columnar junction contains a large pool of cancer-prone immature osteopontin responsive Lgr5−CD44+ cells - Dah-Jiun Fu (Nature Portfolio, 2020)
Cancers arising from the gastric squamous-columnar junction have high incidence and are characterized by a poor prognosis. Here, the authors use genetic mouse models to show that loss of p53 and Rb1 expression results in preferential tumour development at the gastric squamous-columnar junction that contains a large pool of osteopontin responsive Lgr5-CD44+ cells.